Problem solving in organizations : a methodological handbook for business and management students - Aken, Joan Ernst van (Cambridge University Press India Pvt. Ltd., 2011)
"This concise introduction to the methodology of problem solving in organizations is an indispensable guide to the design and execution of practical business improvement projects in real organizational settings. The methodology is design-oriented and theory-informed. It encourages students to use the theory gained in their disciplinary courses by showing them how to do so in a fuzzy, ambiguous and politically charged, real-life organizational context. The book provides an in-depth discussion of the various aspects and steps of the process of business and organizational problem-solving. Rather than presenting the methodology as a recipe to be followed, the authors demonstrate how to adapt the approach to specific situations and to be flexible in scheduling the work at the various steps in the process. It will be indispensable to MBA and other students who venture outside the university walls to do real-life fieldwork"--